Proving the Accuracy and Legal Liability of Clinical Laboratory Examination Results Using Automatic Tools - Yusi Luluk Rahmania; Tjahjono Kuntjoro; Valentinus Suroto (Universitas Katolik Soegijapranata Semarang, 2019)
Laboratorium test is an important aspect of health services. Errors in laboratory results have an impact on physician actions. The need to use an automated device cannot be denied in laboratory services. A high level of public trust in automated device results being difficult to detect if it happens error. On the other hand, reexamination and retrieval specimens cannot prove the accuracy of the laboratory result because it is very unstable.This research was conducted at Roemani Hospital, Awaloedin Djamil Hospital, and BALABKES Jawa Tengah. Interviewees included head of installations/head of laboratories, health analysts, and patients, doctors using laboratory results, and Semarang District Court judges and legal experts.The data was processed descriptively analytically with a sociological juridical approach. Laboratory examination is a process so that each stage must be verified. Documents can be used as evidence that a laboratory conducts examinations following professional standards and SOPs. The laboratory must have documents on each examination procedure from the initial sample received until the results come out which can later be used as evidence in the trial. The storage of these documents has not been regulated so that the formulation is adjusted to Undang-Undang No. 43 of 2009 tentang Arsip and Peraturan Menteri Kesehatan No. 30 of 2012 tentang Jadwal Retensi Arsip Substantif dan Fasilitatif non-Keuangan dan Non-Kepegawaian di Lingkungan Kementerian Kesehatan for documents non-medical records. Laboratorium document that includes a medical record formulated based on Peraturan Menteri Kesehatan No. 269 of 2008 tentang Rekam Medis. From the laboratory studied, it has carried out maintenance of evidence, but it is not good and documentation is still incomplete. The responsibility for civil error results includes the source of the error. Patient non-compliance is the patient's responsibility, while the errors of health analysts and automated tools are the responsibility of the laboratory organizer.